Mechanical, thermal, and environmental testing and performance of ceramic composites and components - Jenkins, Michael G., 1958-; Lara-Curzio, Edgar, 1963-; Gonczy, Stephen T., 1947- (STP Ser. ;, 2000)
Contains 21 papers from a May 1999 symposium on continuous fiber- reinforced advanced ceramic composites, related tests methods, materials characterization, and design applications. Papers are divided into four major categories of room-temperature test results and methods, test results and methods related to design implications, environmental effects and characterization, and damage accumulation and material development. Specific topics include notch-sensitivity of a woven oxide/oxide ceramic matrix composite, effects of microstructural damage on the thermal diffusivity of continuous fiber- reinforced ceramic matrix composites, and degradation of continuous fiber ceramic matrix composites under constant load conditions. The editors are affiliated with the University of Washington; Oak Ridge National Laboratory; and Gateway Materials Technology. Annotation copyrighted by Book News, Inc., Portland, OR.